Safeguarding in Social Work Practice A Lifespan Approach - Chisnell, Charlotte; Kelly, Caroline (London : Learning Matters, 2019)
This text brings together common themes and knowledge in safeguarding across children, young people and adult social work to help students understand how the theory relates to practice and to approach safeguarding from a holistic perspective.
Previous edition: 2016.
Includes bibliographical references and index.
Keywords: Social service; Society